The Effect of a Dilemma on the Relationship Between Ability to Identify the Criterion (ATIC) and Scores on a Validated Situational Interview - Latham, Gary P.; Itzchakov, Guy (Frontiers in Psychology, 2021)
Four experiments were conducted to determine whether participants’ awareness of the performance criterion on which they were being evaluated results in higher scores on a criterion valid situational interview (SI) where each question either contains or does not contain a dilemma. In the first experiment there was no significant difference between those who were or were not informed of the performance criterion that the SI questions predicted. Experiment 2 replicated this finding. In each instance the SI questions in these two experiments contained a dilemma. In a third experiment, participants were randomly assigned to a 2 (knowledge/no knowledge provided of the criterion) X 2 (SI dilemma/no dilemma) design. Knowledge of the criterion increased interview scores only when the questions did not contain a dilemma. The fourth experiment revealed that including a dilemma in a SI question attenuates the ATIC-SI relationship when participants must identify rather than be informed of the performance criterion that the SI has been developed to assess.